The Effect Of Capital Structure And Profitability On The Value Of Registered Pharmaceutical Sector Manufacturing Companies Indonesia Stock Exchange - Asri Jaya; Abdul Wahab; Nurlina Nurlina (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This research aims to investigate the influence of capital structure and profitability variables on the company value within the pharmaceutical sector, focusing on firms listed on the Indonesia Stock Exchange from 2016 to 2020. The study encompasses all Manufacturing Companies in the Pharmaceutical Sector listed on the IDX during this period, with a purposive sampling method selecting 11 companies. Utilizing a descriptive verification approach with a quantitative methodology, the research involved analyzing data through validity testing, multiple linear regression analysis, and hypothesis testing using the t-test. The findings revealed that the capital structure, represented by DAR, exhibited a substantial and meaningful impact on firm value. On the other hand, the study found that profitability, as proxied by ROA, did not exert any significant influence on firm value. These outcomes shed light on the intricate dynamics within the pharmaceutical sector, emphasizing the significance of capital structure in determining firm value while indicating that profitability, as measured by ROA, may not be a sole determinant of firm value in this context. Further research could delve into exploring additional variables and their potential impact on company value within this sector.